Studies in Islamic law, religion, and society - Bhatia, Harbans Singh, 1915- (New Delhi : Deep & Deep Publications, 1989)
Contributed articles.
Includes index.
Bibliography: p. [440]-441.
Keywords: Islam; Islamic law